Unpacking excessive polypharmacy patterns among individuals living with chronic pain in Quebec: a longitudinal study - De Clifford-Faugère, Gwenaelle; Nguena Nguefack, Hermine Lore; Ménard, Nancy; Beaudoin, Sylvie; Pagé, M. Gabrielle; Guénette, Line; Hudon, Catherine; Samb, Oumar Mallé; Lacasse, Anaïs (Frontiers in Pain Research, 2025)
IntroductionExcessive polypharmacy, which can be defined as the concurrent use of ≥10 medications, is prevalent among individuals with chronic pain. However, it remains unclear how it may vary between individuals or over time.ObjectivesThis study aimed to describe and identify factors associated with trajectories of excessive polypharmacy.MethodsA retrospective longitudinal study was conducted using the TorSaDE Cohort, which links Canadian Community Health Surveys (2007–2016) and Quebec health administrative databases. Among 9,156 adults living with chronic pain and covered by public prescribed drug insurance, the presence of excessive polypharmacy (yes/no) was assessed monthly for one-year post-survey completion (12 time points). Group-based trajectory modelling was applied to identify groups with similar patterns over time (trajectories). Multivariable multinomial regression was used to identify factors associated with trajectory membership.ResultsFour trajectories were obtained: (1) “No excessive polypharmacy” (74.8%); (2) “Sometimes in excessive polypharmacy” (8.6%); (3) “Often in excessive polypharmacy” (6.1%); 4) “Always in excessive polypharmacy” (10.5%). Factors associated with the “always in excessive polypharmacy” trajectory membership were: being older, being born in Canada, having a lower income, having a higher comorbidity index score, more severe pain intensity, and more daily activities prevented by pain, reporting arthritis or back pain and poorer perceived general health, and having a family physician. Using opioids or benzodiazepines, having a lower alcohol consumption, doing less physical activity, a higher number of prescribers and visits to a family physician also predicted being always in excessive polypharmacy.DiscussionThis study identifies distinct trajectories of excessive polypharmacy in adults with chronic pain, emphasizing key sociodemographic and clinical factors and the need for tailored interventions for effective medication management.